Learning numeracy using new Pempek mathematics - Putri, Ratu Ilma Indra; Zulkardi; Sari, Novita; Sagita, Laela; Siligar, E. I. Pusta; Sukma, Yovika (Journal on Mathematics Education, 2025)
This study addresses the challenges faced by students in comprehending and articulating the concepts of cost, selling price, and profit, despite their ability to perform related calculations. Contributing factors include a limited learning context and a didactic approach that often prioritizes rote memorization of formulas, thereby hindering a deeper understanding of these concepts. The objective of this research is to design a learning trajectory utilizing the context of New Pempek Mathematics, an innovative adaptation of the traditional Pempek dish, represented in geometric forms such as cones, trapezoidal prisms, cuboids, and cubes, to facilitate students' understanding of cost price, selling price, and profit. The study employs a design research methodology, consisting of three stages: preliminary design, experimental design, and retrospective analysis. The study involved 31 junior high school students from Belitang, Indonesia. Data collection was conducted using a variety of instruments, including student worksheets, video recordings of lessons, interviews with students, and photographs of their presentation work. The proposed learning trajectory, centered around the New Pempek Mathematics production project, emphasizes activities such as identifying cost prices, estimating selling prices, and calculating profit. The findings indicate that integrating mathematics with local cultural contexts, such as New Pempek Mathematics, enhances student engagement and makes the learning experience more relevant, thus improving students' understanding of these fundamental economic concepts.